Individualizing dual antiplatelet therapy duration: Prediction tools, genomics, and clinical judgment. Issue 1 (13th July 2017) - Chatterjee, Arka; Hillegass, William B.
Key Points: Prolonged dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) on average reduces the risk of subsequent myocardial infarction (MI) but increases major bleeds. Individualizing duration of DAPT based on the DAPT trial's net benefit prediction tool would likely optimize outcome beyond population average recommendations. Individualizing agent selection and duration of therapy based on genomic data may further improve outcomes. Clinical judgment remains the most important tool to tailor DAPT duration based on a large array of additional relevant factors not captured by predition rules or genomics.